Molecular Diagnostic of Ochratoxin A With Specific Aptamers in Corn and Groundnut via Fabrication of a Microfluidic Device - Shahdeo, Deepshikha; Khan, Azmat Ali; Alanazi, Amer M.; Bajpai, Vivek K.; Shukla, Shruti; Gandhi, Sonu (Frontiers in Nutrition, 2022)
Ochratoxin A (OTA) is one of the predominant mycotoxins that contaminate a wide range of food commodities. In the present study, a 36-mer aptamer was used as a molecular recognition element coupled with gold nanoparticles (AuNPs) for colorimetric detection of OTA in a microfluidic paper-based analytical device (µPADs). The μPADs consisted of three zones: control, detection, and sample, interconnected by channels. The biophysical characterizations of aptamer conjugated AuNPs were done by UV-vis spectroscopy (UV-vis), dynamic Light Scattering (DLS), and transmission electron microscopy (TEM). The developed colorimetric assay for OTA showed a limit of detection of 242, 545, and 95.69 ng/mL in water, corn, and groundnut, respectively. The HPLC detection method achieved acceptable coefficient in standard curves (r2 = 0.9995), better detection range, and recovery rates in spiked corn and groundnut samples as 43.61 ± 2.18% to 87.10 ± 1.82% and 42.01 ± 1.31% to 86.03 ± 2.64% after multiple sample extractions and cleanup steps. However, the developed μPADs analytical device had the potent ability to rapidly detect OTA without any extraction pre-requirement, derivatization, and cleanup steps, thus illustrating its feasibility in the animal health sector, agricultural, and food industries.